Geographic Linkage and Variation in Cryptosporidium hominis - Rachel M. Chalmers; Stephen J. Hadfield; Colin J. Jackson; Kristin Elwin; Lihua Xiao; Paul Hunter (Emerging Infectious Diseases, 2008)
UK Cryptosporidium hominis isolates have previously shown slight PCR fragment length polymorphism at multiple loci. To further investigate transmission, we conducted a case–control study and sequenced the GP60 locus from 115 isolates. Nine subtypes were identified; IbA10G2 predominated. Having a non-IbA10G2 subtype was significantly linked to recent travel outside Europe.